Calix[4]arene C-99 inhibits myosin ATPase activity and changes the organization of contractile filaments of myometrium - R. D. Labyntseva,; A. A. Bevza; A. О. Lul’ko; S. О. Cherenok; V. I. Kalchenko; S. О. Kosterin (The Ukrainian Biochemical Journal, 2015)
Calix[4]arenes are cup-like macrocyclic (polyphenolic) compounds, they are regarded as promising molecular “platforms” for the design of new physiologically active compounds. We have earlier found that сalix[4]arenе C-99 inhibits the ATPase activity of actomyosin and myosin subfragment-1 of pig uterus іn vitro. The aim of this study was to investigate the interaction of calix[4]arene C-99 with myosin from rat uterine myocytes. It was found that the ATPase activity of myosin prepared from pre-incubated with 100 mM of calix[4]arene C-99 myocytes was almost 50% lower than in control. Additionally, we have revealed the effect of calix[4]arene C-99 on the subcellular distribution of actin and myosin in uterus myocytes by the method of confocal microscopy. This effect can be caused by reorganization of the structure of the contractile smooth muscle cell proteins due to their interaction with calix[4]arene. The obtained results demonstrate the ability of calix[4]arene C-99 to penetrate into the uterus muscle cells and affect not only the myosin ATPase activity, but also the structure of the actin and myosin filaments in the myometrial cells. Demonstrated ability of calix[4]arene C-99 can be used for development of new pharmacological agents for efficient normalization of myometrial contractile hyperfunction.